Peripapillary choroidal vascularity index and thickness in patients with systemic sclerosis - Pieklarz, Barbara; Gińdzieńska-Sieśkiewicz, Ewa; Zawadzka, Izabela; Bagrowska, Magdalena; Daniluk, Joanna; Sidorczuk, Patryk; Kowal-Bielecka, Otylia; Konopińska, Joanna; Dmuchowska, Diana Anna (Frontiers in Medicine, 2023)
Introduction Patients with systemic sclerosis (SSc) present an increased risk of developing glaucomatous optic neuropathy (GON). We investigated peripapillary choroidal parameters and peripapillary retinal nerve fiber layer (RNFL) thickness using spectral domain optical coherence tomography (SD-OCT) to determine the relationships of these factors with clinical variables. Methods A total of 33 patients with SSc were enrolled and compared to 40 controls. After obtaining circular scans around the optic disc, the global and quadrant peripapillary choroidal thickness (pCT) and RNFL thickness were measured. Additionally, the peripapillary choroidal vascularity index (pCVI), which allows for a quantitative analysis of the choroidal vasculature, was determined. Results No significant differences were found in pCT and RNFL thickness between patients with SSc and controls, or within SSc subtypes (diffuse cutaneous systemic sclerosis (dcSSc) compared to limited cutaneous systemic sclerosis (lcSSc)) (p > 0.05). The pCVI was significantly lower in patients with SSc than in control subjects (64.25 ± 1.94 vs.65.73 ± 2.12, p < 0.001). Conclusion Our results suggest that the statistically significant decrease in pCVI in patients with SSc compared to the control group is probably due to a decrease in the vascular layer, which would partially explain an increased risk of GON in patients with SSc.